Collection activity channels selection in a reverse supply chain under a carbon cap-and-trade regulation. (1st July 2020) - Kushwaha, Siddhartha; Ghosh, Arindam; Rao, A.K.
Abstract: Manufacturers face challenges while collecting used products in their reverse supply chain from several scattered geographic regions. These regions are different in terms of quality of used products returned, quantity returned, the timing of the returns, and regions' distance from the central remanufacturing facility. The paper proposes a mixed-integer linear programming model for such manufacturer to decide on an optimal combination of channels for collecting used products from these regions in a finite multi-period situation. In each region the manufacturer has two potential sources of collection activity for the manufacturer are −1) through a regional independent collection firm, and 2) direct collection from regional customers. The decision problem is considered under constrains of the quantity and quality of returned products, carbon emission cap-and-trade regulation. A numerical analysis using parameter value estimated using field studies in India for steel drums is presented. The results of the analysis suggest that manufacturers and carbon policymakers should consider the quantity of returned product over the product life cycle. Further, the target for long term carbon emission reduction has implication to a manufacturer's channels selection for collection activity from multiple regions. Results of analysis also indicate the effect of timing for carbon-cap-and-trade policy implementation on the selection of channels for collection activity in a multi-region problem. Highlights: Used products Collection from multiple regions with different characteristics. Multi-channels selection under carbon cap-and-trade constraint. A field study of reverse supply chain channel for steel drums in India. Carbon cap-and-trade policy holiday till end of growth stage in product life cycle. Target for long term carbon emissions reduction inflences the channels selection.